2017
DOI: 10.1079/pavsnnr201712007
|View full text |Cite
|
Sign up to set email alerts
|

Halal food certification in the UK and its impact on food businesses: a review in the context of the European Union.

Abstract: The majority of Muslims only consume Halal food because they believe the consumption of such foods is a commandment from Allah (God). Whilst Halal food may be readily available in Muslim-majority countries, Muslims living in the West often encounter a great deal of difficulty in finding Halal food. This led to the establishment of several unregulated Halal Certification Bodies (HCBs) within the European Union and other industrialized economies in an effort to assure Halal consumers that Halal certified product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Notable among the differences seen are; the acceptability of stunning, the acceptability of mechanical slaughter, the acceptability of thoracic (chest sticking) for large ruminants and the permissibility of meat from animals slaughtered by individuals other than a Muslim. Fuseini (2017) suggested that the Halal sector urgently needs a system of monitoring or accrediting HCBs to ensure that these organisations implement robust quality management systems to increase integrity and to increase consumer confidence. The Halal Monitoring Committee (HMC) and Halal Food Authority (HFA) are the two oldest HCBs in the UK and certify the majority of food businesses.…”
Section: Halal Certification: the Uk As A Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Notable among the differences seen are; the acceptability of stunning, the acceptability of mechanical slaughter, the acceptability of thoracic (chest sticking) for large ruminants and the permissibility of meat from animals slaughtered by individuals other than a Muslim. Fuseini (2017) suggested that the Halal sector urgently needs a system of monitoring or accrediting HCBs to ensure that these organisations implement robust quality management systems to increase integrity and to increase consumer confidence. The Halal Monitoring Committee (HMC) and Halal Food Authority (HFA) are the two oldest HCBs in the UK and certify the majority of food businesses.…”
Section: Halal Certification: the Uk As A Case Studymentioning
confidence: 99%
“…These additional requirements on meat exported to the major Halal markets and the readiness of Halal meat exporters to comply, has highlighted the significance of Halal certification to exporters. Fuseini (2017) noted that Halal consumers generally regard HCBs as the enforcers of the Islamic dietary laws and that they give consumers assurance that Halal certified products meet these laws as enshrined in Islamic scriptures. However, there appear to be differences in opinion among HCBs with regard to the acceptability of certain practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, takaful and Halal tourism constitute an emerging area of interest in the market because of its implications on many attractive segments of market (Battour and Ismail, 2016;Chanin et al, 2015;Ngah et al, 2014). From food to financial markets, businesses have greatly benefited by adhering to the Islamic principles to attract more and more Muslim consumers (Fuseini, 2017;Aysan et al, 2018). Takaful, the Islamic mode of insurance, confirms to the Islamic principles of economics and transactions.…”
mentioning
confidence: 99%
“…Finally, many studies that have dealt with empirical analysis and country case studies, have referred to the Malaysian halal ecosystem. Only a few exceptions have carried out research relating to EU countries (Ahmed, 2008; Campbell et al , 2011; Fuseini, 2017; Lever and Miele, 2012). To the best of our knowledge, few studies have considered the state of halal food production and markets in Italy.…”
Section: Literature Reviewmentioning
confidence: 99%